(untitled) (Scientific journal of the Fergana State University, 2024)
The article reflects methods of teaching students in a team, planning educational skills, organizing classes in groups, leadership and control, control. It is explained that computer science teachers can improve their lessons by applying team learning technologies to the digital process and achieve positive learning outcomes.